Sowing method of radices gentianae dahuricae - MENG XINGYE; YANG SHUGUANG; LI MINHUI; XU JIANPING; ZHANG CHUNHONG; YI LETAI (2019)
A sowing method of radices gentianae dahuricae includes the following steps that 1, seed selection is performed, wherein wild radices gentianae dahuricae seeds are harvested in early September and October of the current year; 2, seed treatment is performed, wherein wild radices gentianae dahuricae seeds harvested in early and middle February of the next year are mixed evenly with sand in the ratioof 1:(30-35), the mixture is placed in jute bags in cellars or shade and buried in snow for variable temperature storage; 3, land selection and soil preparation are performed, sandy loam with high topography, good drainage and strong permeability is selected, and soil preparation, raking and flood irrigation and penetration are performed in autumn the year before sowing; 4, open-field sowing is performed, wherein sowing is performed in early June and July, broadcast sowing is adopted, seeds are blended with fine sand, a layer of fine sand is used for covering after sowing, and watering is needed timely to keep a seed